Learning to Let Go: A Cognitive-Behavioral Model of How Psychedelic Therapy Promotes Acceptance - Wolff, Max; Evens, Ricarda; Mertens, Lea J.; Koslowski, Michael; Betzler, Felix; Gründer, Gerhard; Jungaberle, Henrik (Frontiers in Psychiatry, 2020)
The efficacy of psychedelic-assisted therapies for mental disorders has been attributed to the lasting change from experiential avoidance to acceptance that these treatments appear to facilitate. This article presents a conceptual model that specifies the psychological mechanisms underlying such change, and that shows substantial parallels between psychedelic therapy and cognitive behavioral therapy: We propose that under the carefully controlled conditions of psychedelic therapy as applied in contemporary clinical research, psychedelic-induced belief relaxation can increase motivation for acceptance via operant conditioning, thus engendering episodes of relatively avoidance-free exposure to greatly intensified private events. Under these unique learning conditions, relaxed avoidance-related beliefs can be exposed to corrective experiences and become revised accordingly, which may explain to long-term increases in acceptance and corresponding reductions in psychopathology. Open research questions and implications for clinical practice are discussed.